The history of nature conservation between 1971 and 1975 (designation of protected areas) - Centeri, Csaba; Gyulai, Ferenc (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
Following the previous examined period (1966–1970.) there were 3908 designations of protected areas between 1971 and 1975 on Earth. One third of these designations belong to the IUCN category III while another third belongs to the IUCN category IV. Data analyzed in the article is based on the protected areas listed in the IUCN database. According to that most of the designations (779) were in Ukraine between 1971 and 1975. In the present five analyzed years (1971–1975) the growth of the designations stopped, there were less areas designated than in the previous five year period. In the analyzed period of 1971 and 1975 220 national categories existed. Among the size of the areas the 0–99 ha areas outnumbered all other (almost half of the designated areas belong to this size), however only 0,015% of all established protected area belongs here from the spatial distribution point of view. 14 Hungarian protected areas appear in the IUCN database in this period. An important action took place in this period, the establishment of the first Hungarian national park on the Hortobágy area in 1973. Two areas have extreme sizes in this period. One of them is the North East Greenland National Park with 97.2 million hectare. The other area is the Great Barrier Reef Marie Park in Australia with its 34.4 million hectare area. We can state that this period was outstanding from the point of view of area enlargements of the protected areas.
Keywords: nature conservation; history; world; protected areas; 1971–1975